Modernisasi Dalam Pendidikan Islam: Kajian Komparatif Pendidikan Islam Mesir dan Indonesia - Ariatman, Roby; Mukhlis; Jamaludin (Kariman: Jurnal Pendidikan Keislaman, 2024)
The focus of this research is to analyze how Islamic education in Egypt and Indonesia responds to the challenges of modernization in the context of Islamic education. This research uses a qualitative approach with a library research method sourced from various literatures, such as books, scientific articles, and related official documents. Through content analysis of the collected literature, this study found that the modernization of Islamic education in Egypt emphasizes more on maintaining traditional or classical learning while adopting modern technology and curriculum. Meanwhile, in Indonesia modernization is more integrative, where traditional elements and educational innovations are adaptively combined. This study is expected to provide new insights into how Islamic education can develop contextually amid the demands of global modernity.